2016
DOI: 10.1073/pnas.1609592113
|View full text |Cite
|
Sign up to set email alerts
|

VEGF preconditioning leads to stem cell remodeling and attenuates age-related decay of adult hippocampal neurogenesis

Abstract: Several factors are known to enhance adult hippocampal neurogenesis but a factor capable of inducing a long-lasting neurogenic enhancement that attenuates age-related neurogenic decay has not been described. Here, we studied hippocampal neurogenesis following conditional VEGF induction in the adult brain and showed that a short episode of VEGF exposure withdrawn shortly after the generation of durable new vessels (but not under conditions where newly made vessels failed to persist) is sufficient for neurogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 55 publications
(75 reference statements)
1
53
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) may mediate exercise-induced vascular plasticity, adult neurogenesis, and communication between peripheral tissues and brain (Carmeliet 2003; Fabel et al 2003; Cotman et al 2007; Udo et al 2008). VEGF is involved in blood vessel formation (Prior et al 2003; Gavin et al 2004; Kraus et al 2004) and can attenuate the aged-related decline in neurogenesis (Licht et al 2016). The importance of VEGF for neurogenesis was first shown in songbirds.…”
Section: Cerebrovascular Plasticitymentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) may mediate exercise-induced vascular plasticity, adult neurogenesis, and communication between peripheral tissues and brain (Carmeliet 2003; Fabel et al 2003; Cotman et al 2007; Udo et al 2008). VEGF is involved in blood vessel formation (Prior et al 2003; Gavin et al 2004; Kraus et al 2004) and can attenuate the aged-related decline in neurogenesis (Licht et al 2016). The importance of VEGF for neurogenesis was first shown in songbirds.…”
Section: Cerebrovascular Plasticitymentioning
confidence: 99%
“…Some NSCs are short-lived and divide rapidly to mainly produce granule neuronsexhibiting "division-coupled differentiation" behavior (Encinas et al, 2011) or "developmental-like model" behavior (Pilz et al, 2018). Meanwhile, some studies (Bonaguidi et al, 2011;Dranovsky et al, 2011;Jang et al, 2013;Licht et al, 2016) have advanced a stem cell maintenance model where NSCs are longer lived, slowly cycle in and out of quiescence, can generate neurons, astrocyte and self-renew. We reasoned that cellular heterogeneity within the radial glial-like NSC pool masks the ability to precisely uncover which mechanisms contribute to NSC dysfunction over time (Bonaguidi et al, , 2016.…”
Section: Asynchronous Nsc Decline During Agingmentioning
confidence: 99%
“…Consistently, forced accelerated neurogenesis (Ehm et al, 2010;Jones et al, 2015;Renault et al, 2009) and pathological conditions (Mu and Gage, 2011;Sierra et al, 2015) can result in premature NSC depletion. In another scenario, studies (Bonaguidi et al, 2011;Dranovsky et al, 2011;Licht et al, 2016) have shown that self-renewing NSCs are maintained and neurogenesis instead could decline during aging due to an increase in NSC quiescence (Hattiangady and Shetty, 2008;Ziebell et al, 2018). While NSCs as a population clearly undergo early age-related changes, when and how specific NSC subpopulation begin to exhibit dysfunction remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since norvaline elevates NOS3 levels [16], we suggest a significant involvement of VEGF activation in the phenotype observed following norvaline treatment. VEGF is essential for neuroprotection [22], and its activation is beneficial for individuals with early signs of AD-associated dementia [23].VEGF preconditioning has been shown to attenuate age-related decay of adult hippocampal neurogenesis in mice [24]. Additionally, the administration of VEGF in rats with focal cerebral ischemia reduces the infarct size and enhances neurogenesis [25].…”
mentioning
confidence: 99%
“…VEGF preconditioning has been shown to attenuate age-related decay of adult hippocampal neurogenesis in mice [24]. Additionally, the administration of VEGF in rats with focal cerebral ischemia reduces the infarct size and enhances neurogenesis [25].…”
mentioning
confidence: 99%